Efectiveness of Argumentation Flipped Learning (AFL) Assisted by Macromedia Flash Software to Improve Student’s Understanding of Physics Concepts - Akhdinirwanto, Raden Wakhid; Hikmah, Nur; Maftukhin, Arif (JIPF (Jurnal Ilmu Pendidikan Fisika), 2024)
The objective of this research was to assess the validity, practicality, and effectiveness of enhancing students' comprehension of physics concepts. The research uses the Research and Development (R&D) method use ADDIE model. This research was conducted in Physics Education of Muhammadiyah Purworejo University with the research subjects of 4th semester students in a limited trial of 5 students and a broad trial of 8 students. The instruments used in this study were lesson plan validation sheet, media validation sheet, lesson plan implementation sheet, student activity sheet, physics concept understanding test sheet, scoring rubric, student response questionnaire, and notes on educational activities. Data evaluation techniques were quantitative, N-gain, and T-Test. The results of the study obtained (1) the validity of the application of the AFL model assisted by macromedia flash software was declared valid, (2) the practicality of the application of the AFL model assisted by macromedia flash software, as seen from the implementation of the lesson plan obtained an average of 3.72 in the good category and the reliability test was 93%, (3) the effectiveness of the application of the AFL model assisted by macromedia flash software, as seen from the results of increasing concept understanding obtained N-gain value of 0.68 which is included in the moderate category, response questionnaire with good category, and student activity with good category. It is concluded that the application of AFL model assisted by macromedia flash software is valid, practical, and effective.